Recursive group coding for image DCT compression efficiency - Kozhemiakina, Nadejda; Lukin, Vladimir; Ponomarenko, Nikolay; Naumenko, Victoria (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The problem of encoding information in order to eliminate its statistical redundancy has been considered. The most widespread techniques for lossless encoding are arithmetic and Huffman coding. One disadvantage of these methods is the lack of efficiency when encoding characters with extra-large alphabets. In this paper, the efficiency of image data compression with method of recursive group coding has been considered and compared to arithmetic and Huffman coding. It is shown that recursive group coding provides a sufficient gain in compression compared to aforementioned methods.